Communication cable sheath material and preparation process thereof
By mixing the organic sol with silica sol and processing it at high temperature to form a graphite mesh, and then compounding it with polyvinyl alcohol, the shortcomings of cable sheath material in terms of fire resistance, heat resistance, flame retardant and mechanical properties are solved, and high Performance communication cable sheath material.
Patent Information
- Application Number
- CN202411305298.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-02-07
AI Technical Summary
The existing cable sheath materials have shortcomings in fire resistance, heat resistance, flame retardant and mechanical properties, making it difficult to effectively deal with the mechanical stress and fire risks of cables in high voltage and high temperature environments.
Organic sol and silica sol are mixed, and after aging, spinning, drying, braiding and high temperature treatment, they form graphite mesh, and then compounded with polyvinyl alcohol to prepare a communication cable guard with heat resistance, flame retardant and high mechanical properties. Set of materials.
The material is heat-resistant, flame-retardant and high mechanical properties, enhance the fire-resistant performance of the cable, and reduce property losses and life dangers caused by fire.
Smart Images

Figure BDA0005048990790000081 
Figure BDA0005048990790000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable sheaths, in particular to a communication cable sheath material and a preparation process thereof. Background Art
[0002] With the rapid development of social economy, the demand for electricity in my country is growing rapidly; and with the unprecedented development of subways, nuclear power plants, optoelectronic communications and other fields, the consumption of electricity is also growing rapidly. As a major power transmission and communication medium, cables have high voltage transmission capacity, lightness, flexibility and anti-interference ability, and play a vital role in modern society. When designing a system, cables are often the last part to be considered. In many cases, cables are lifelines. For example, if the cable that transmits data on a spacecraft fails, the spacecraft and the ground control center will lose communication. The reliability of a cable is mainly based on its durability and signal integrity. Bending can generate kinetic energy in the cable, which can cause serious damage if not properly handled; when the cable is part of the worker's operating equipment, it is most likely to cause mechanical stress to the cable. When the operator steps on or flips the cable, it is possible to kink, fold or crush the cable; therefore, the cable's anti-extrusion and anti-tensile strength are essential to overcome mechanical stress.
[0003] However, there are certain safety hazards in the use of cables, one of which is the fire prevention of cables. If cables are overloaded for a long time, the current inside the cables will be too large, the internal insulation layer of the cables will be damaged or the external insulation layer will be broken, resulting in a short circuit in the cables, causing the cables to heat up, and eventually lead to fires, and release toxic and harmful gases to cause serious harm or even endanger lives, often accompanied by the spread of fire, which can easily cause huge property losses; cable fire prevention is not only related to the safety of people's lives and property, but also an important part of ensuring the normal operation of society. Summary of the invention
[0004] The object of the present invention is to provide a communication cable sheath material and a preparation process thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a communication cable sheath material, which is prepared by mixing an organic sol and a silica sol, aging, spinning, drying, weaving, and high-temperature treatment to obtain a graphite mesh, which is then compounded with polyvinyl alcohol.
[0006] Furthermore, a method for preparing a communication cable sheath material comprises the following preparation steps:
[0007] (1) mixing an organic sol, a silica sol, and 3-aminopropyltrihexyloxysilane, heating the mixture to 67-72°C at 10°C at a rate of 2-3°C / h, performing gel aging treatment, and then wet spinning the mixture into a deionized water coagulation bath, coagulating for 1-3 hours, removing the mixture, immersing the mixture in tert-butyl alcohol, standing the mixture for 3-6 hours, rinsing the mixture with deionized water for 5-10 times, drying the mixture with carbon dioxide supercritical fluid, and weaving the mixture into a web to obtain an aerogel fiber web;
[0008] (2) The aerogel fiber web is carbonized and then placed in a 4 wt % boric acid aqueous solution for 4 to 7 h, dried at 80 to 100 ° C. for 100 to 160 min, and then heated to 2400 to 3000 ° C. at 8 to 15 ° C. / min in a nitrogen atmosphere for graphitization for 18 to 30 s to obtain a graphite fiber web;
[0009] (3) The graphite fiber mesh is pretreated under ultraviolet conditions of 254 nm, and then doped polyvinyl alcohol is coated on both sides of the graphite fiber mesh. The mesh is irradiated for 10 to 20 minutes under a microwave power of 200 to 400 W, and cured at 60 to 85° C. for 70 to 150 minutes to obtain a communication cable sheath material.
[0010] Furthermore, the preparation method of the organosol described in step (1) is as follows: sodium hydroxide, urea and deionized water are mixed in a mass ratio of 7:12:100, cooled to 10-15°C, short cotton wool with a mass of 0.3-0.6 times that of sodium hydroxide and chitosan with a mass of 0.08-0.12 times that of sodium hydroxide are added, stirred at 200-500rpm for 10-20min, then sheared at 100-200rpm for 15-30min, sodium periodate with a mass of 0.04 times that of sodium hydroxide is added, stirred at 70-120rpm for 10min, 8wt% o-phthalaldehyde-ethanol solution with a mass of 8-12 times that of sodium hydroxide is added, and stirring is continued for 10min.
[0011] Furthermore, the process parameters of the wet spinning in step (1) are: spinneret aperture of 0.07-0.12 mm, spinning speed of 200-350 m / min.
[0012] Furthermore, in step (1), the temperature of the carbon dioxide supercritical fluid drying is 50-65° C. and the gas pressure is 13-19 MPa.
[0013] Furthermore, the weight of the mesh in step (1) is 70 to 100 g / m 2 .
[0014] Furthermore, the mass ratio of the organic sol, silica sol and 3-aminopropyltrihexyloxysilane in step (1) is 7:7:1.
[0015] Furthermore, the carbonization step in step (2) is carried out at a flow rate of 40 to 60 m 3 / h in an argon environment, heat up to 700-850°C at 5-12°C / min, keep warm for 2.5-4h, continue to heat up to 1400°C, keep warm for 5h, continue to heat up to 1500°C, keep warm for 5h.
[0016] Furthermore, the pretreatment conditions in step (3) are: ozone concentration of 50 mg / L, temperature of 100-150° C., and time of 1-5 min.
[0017] Furthermore, the doped polyvinyl alcohol in step (3) is prepared from polyvinyl alcohol 1799, magnesium hydroxide, low-density polyethylene 2426H, diisopropylbenzene peroxide, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] in a mass ratio of 8-20:1.5-3:80-90:0.05-0.1:0.05-0.2.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0019] The material of the invention is prepared by mixing an organic sol and a silicon dioxide sol, and undergoing aging, spinning, drying, weaving, and high-temperature treatment to obtain a graphite mesh, which is then compounded with polyvinyl alcohol to achieve the effects of heat resistance, flame retardancy, and high mechanical properties.
[0020] First, an organic sol is prepared using a rigid cross-linking agent, o-phthalaldehyde, and used as a carbon source to mix with a silica sol as a silicon source. The hydroxyl groups on the cellulose molecular chain react with the aldehyde groups in the o-phthalaldehyde molecule to form a cross-linking chemistry, and a non-covalent bond interaction is formed between the silica and the cellulose molecular chains, and the mesopores and macropores in the cellulose structure are filled, making the hybrid aerogel more compact and more complete in structure. After gel aging, a network structure with excellent three-dimensional skeleton is formed, thereby giving the matrix stronger mechanical properties. Then, an aerogel fiber mesh is obtained through spinning, drying, and weaving, and then spun in flowing argon gas. Through solid-gas reaction and carbon thermal reduction reaction, a silicon carbide layer is formed on the skeleton surface of the composite aerogel. As the temperature rises, uniformly dispersed silicon carbide nanoparticles are formed in the matrix, thereby forming a network carbon, silicon dioxide, and silicon carbide ternary aerogel, which makes the matrix flame retardant. Then, high temperature is used again to realize fiber graphitization, and a trace amount of boron is introduced in this process to produce a protective effect on the fiber surface, reducing the peeling of the fiber surface to a certain extent, and then entering the graphite matrix to fill the gaps between the hexagonal rings, thereby improving the crystallinity and graphitization degree, thereby enhancing the flame retardancy, heat resistance and mechanical properties.
[0021] Secondly, ozone is used to pretreat the fiber web. Under the action of ultraviolet rays, the new ecological oxygen released by the decomposition of ozone is promoted, so that the surface of the graphite fiber is fully oxidized and the surface area and roughness of the fiber are increased. These grooves serve as the meshing points of the coating on the fiber surface, increasing the mechanical bite effect on the interface, which is beneficial to improving the interface performance of the composite material. After treatment, the oxygen and nitrogen content on the fiber surface increases, and a large number of oxygen-containing polar groups are formed on the fiber surface, which improves its wettability with the resin and further enhances its chemical bonding with the resin; then, linear polymer polyvinyl alcohol doped with magnesium hydroxide is composited on both sides of the web. Under the action of microwave irradiation, the movement of polyvinyl alcohol molecules is promoted, and magnesium hydroxide is driven into the micropores of the aerogel. Through curing condensation, an effect similar to physical chain entanglement is achieved, thereby enhancing the heat resistance, flame retardancy and mechanical properties of the material. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of the communication cable sheath material produced in the following examples:
[0024] Flame retardancy: The same size of the embodiment and the comparative example were subjected to the UL94 vertical combustion test and the coating LOI was detected.
[0025] Mechanical properties: The same size of the embodiment and the comparative example were taken according to GB / T1040 to test their tensile strength and elongation at break.
[0026] Heat resistance: Take the same size of the embodiment and the comparative example and refer to GB / T2951.12, and conduct a heat aging test at 150°C for 24h, and then test the tensile strength and elongation at break.
[0027] Example 1
[0028] (1) Sodium hydroxide, urea, and deionized water were mixed in a mass ratio of 7:12:100, cooled to 10°C, short cotton wool 0.3 times the mass of sodium hydroxide and chitosan 0.08 times the mass of sodium hydroxide were added, stirred at 200 rpm for 10 min, then sheared at 100 rpm for 15 min, sodium periodate 0.04 times the mass of sodium hydroxide was added, stirred at 70 rpm for 10 min, 8 wt% o-phthalaldehyde-ethanol solution 8 times the mass of sodium hydroxide was added, and stirring was continued for 10 min to obtain Organic sol; the organic sol, silica sol and 3-aminopropyl trihexyloxysilane are mixed, heated at 10°C to 67°C at a rate of 2°C / h, and subjected to gel aging treatment, followed by wet spinning with a spinneret aperture of 0.07mm and a spinning speed of 200m / min, in a deionized water coagulation bath, coagulated for 1h, fished out, immersed in tert-butyl alcohol, allowed to stand for 3h, rinsed with deionized water 5 times, dried with carbon dioxide supercritical fluid at 50°C and an air pressure of 13MPa, and woven into 70g / m 2 to obtain an aerogel fiber web; the mass ratio of the organic sol, the silica sol, and the 3-aminopropyltrihexyloxysilane is 7:7:1;
[0029] (2) At a flow rate of 40 m 3 / h argon environment, the aerogel fiber web was carbonized, heated to 700 ° C at 5 ° C / min, kept warm for 2.5 h, continued to heat to 1400 ° C, kept warm for 5 h, continued to heat to 1500 ° C, kept warm for 5 h, then placed in 4wt% boric acid aqueous solution, soaked for 4 h, dried at 80 ° C for 100 min, then heated to 2400 ° C at 8 ° C / min in a nitrogen atmosphere, graphitized for 18 s to obtain a graphite fiber web;
[0030] (3) Polyvinyl alcohol 1799, magnesium hydroxide, low-density polyethylene 2426H, diisopropylbenzene peroxide, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] are mixed in a mass ratio of 8:1.5:80:0.05:0.05 to obtain doped polyethylene; a graphite fiber mesh is pretreated at 100° C. for 1 min in an ozone concentration of 50 mg / L and an ultraviolet wavelength of 254 nm, and then the doped polyvinyl alcohol is coated on both sides of the graphite fiber mesh, irradiated for 10 min under a microwave power of 200 W, and cured at 60° C. for 70 min to obtain a communication cable sheath material.
[0031] Example 2
[0032] (1) Sodium hydroxide, urea, and deionized water were mixed in a mass ratio of 7:12:100, cooled to 13°C, short cotton wool 0.5 times the mass of sodium hydroxide and chitosan 0.1 times the mass of sodium hydroxide were added, stirred at 350 rpm for 15 min, then sheared at 15 rpm for 23 min, sodium periodate 0.04 times the mass of sodium hydroxide was added, stirred at 100 rpm for 10 min, 8 wt% o-phthalaldehyde-ethanol solution 10 times the mass of sodium hydroxide was added, and stirring was continued for 10 min to obtain an organic solvent. The organic sol, silica sol and 3-aminopropyl trihexyloxysilane were mixed, heated at 10°C to 70°C at a rate of 2.5°C / h, and subjected to gel aging treatment, followed by wet spinning with a spinneret aperture of 0.1mm and a spinning speed of 250m / min, into a deionized water coagulation bath, coagulated for 2h, fished out, immersed in tert-butyl alcohol, allowed to stand for 4.5h, rinsed with deionized water 8 times, dried with carbon dioxide supercritical fluid at 60°C and an air pressure of 16MPa, and woven into 80g / m 2 to obtain an aerogel fiber web; the mass ratio of the organic sol, the silica sol, and the 3-aminopropyltrihexyloxysilane is 7:7:1;
[0033] (2) At a flow rate of 50 m 3 / h argon environment, the aerogel fiber web was carbonized, heated to 800 ° C at 9 ° C / min, kept warm for 3 h, continued to heat to 1400 ° C, kept warm for 5 h, continued to heat to 1500 ° C, kept warm for 5 h, then placed in 4wt% boric acid aqueous solution, soaked for 5.5 h, dried at 90 ° C for 130 min, then heated to 2700 ° C at 12 ° C / min in a nitrogen atmosphere, graphitized for 25 s to obtain a graphite fiber web;
[0034] (3) Polyvinyl alcohol 1799, magnesium hydroxide, low-density polyethylene 2426H, diisopropylbenzene peroxide, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] are mixed in a mass ratio of 15:2.2:85:0.08:0.1 to obtain doped polyethylene; a graphite fiber mesh is pretreated at 130° C. for 3 min in an ozone concentration of 50 mg / L and an ultraviolet wavelength of 254 nm, and then the doped polyvinyl alcohol is coated on both sides of the graphite fiber mesh, irradiated for 15 min under a microwave power of 300 W, and cured at 75° C. for 110 min to obtain a communication cable sheath material.
[0035] Example 3
[0036] (1) Sodium hydroxide, urea, and deionized water were mixed in a mass ratio of 7:12:100, cooled to 15°C, short cotton wool 0.6 times the mass of sodium hydroxide and chitosan 0.12 times the mass of sodium hydroxide were added, stirred at 500 rpm for 20 min, then sheared at 200 rpm for 30 min, sodium periodate 0.04 times the mass of sodium hydroxide was added, stirred at 120 rpm for 10 min, 8 wt% o-phthalaldehyde-ethanol solution 12 times the mass of sodium hydroxide was added, and stirring was continued for 10 min to obtain Organic sol; the organic sol, silica sol and 3-aminopropyl trihexyloxysilane are mixed, and the temperature is raised from 10°C to 72°C at a rate of 3°C / h for gel aging treatment, and then wet-spun with a spinneret aperture of 0.12mm and a spinning speed of 350m / min, and placed in a deionized water coagulation bath for coagulation for 3h, and then taken out and immersed in tert-butyl alcohol, and allowed to stand for 6h, and then rinsed with deionized water 10 times, and dried with carbon dioxide supercritical fluid at 65°C and an air pressure of 19MPa, and woven into 100g / m 2 to obtain an aerogel fiber web; the mass ratio of the organic sol, the silica sol, and the 3-aminopropyltrihexyloxysilane is 7:7:1;
[0037] (2) At a flow rate of 60 m 3 / h argon environment, the aerogel fiber web was carbonized, heated to 850°C at 12°C / min, kept warm for 4h, continued to heat to 1400°C, kept warm for 5h, continued to heat to 1500°C, kept warm for 5h, then placed in 4wt% boric acid aqueous solution, soaked for 7h, dried at 100°C for 160min, then heated to 3000°C at 15°C / min in a nitrogen atmosphere, graphitized for 30s to obtain a graphite fiber web;
[0038] (3) Polyvinyl alcohol 1799, magnesium hydroxide, low-density polyethylene 2426H, diisopropylbenzene peroxide, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] are mixed in a mass ratio of 20:3:90:0.1:0.2 to obtain doped polyethylene; a graphite fiber mesh is pretreated at 150° C. for 5 min in an ozone concentration of 50 mg / L and an ultraviolet wavelength of 254 nm, and then the doped polyvinyl alcohol is coated on both sides of the graphite fiber mesh, irradiated for 20 min under a microwave power of 400 W, and cured at 85° C. for 150 min to obtain a communication cable sheath material.
[0039] Comparative Example 1
[0040] The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: sodium hydroxide, urea, and deionized water are mixed in a mass ratio of 7:12:100, cooled to 13°C, short cotton wool 0.5 times the mass of sodium hydroxide and chitosan 0.1 times the mass of sodium hydroxide are added, stirred at 350rpm for 15min, then sheared at 15rpm for 23min, sodium periodate 0.04 times the mass of sodium hydroxide is added, stirred at 100rpm for 10min, 8wt% o-phthalaldehyde-ethyl acetate 10 times the mass of sodium hydroxide is added alcohol solution, continue stirring for 10 minutes to obtain an organic sol; mix the organic sol and 3-aminopropyltrihexyloxysilane, heat at 10°C to 70°C at 2.5°C / h, perform gel aging treatment, and then wet-spin with a spinneret aperture of 0.1mm and a spinning speed of 250m / min, into a deionized water coagulation bath, coagulate for 2h, remove, immerse in tert-butyl alcohol, stand for 4.5h, rinse with deionized water 8 times, and perform carbon dioxide supercritical fluid drying at 60°C and an air pressure of 16MPa to weave into 80g / m 2 to obtain an aerogel fiber web; the mass ratio of the organic sol and 3-aminopropyltrihexyloxysilane is 7:1; and the remaining steps are the same as those in Example 2.
[0041] Comparative Example 2
[0042] The difference between Comparative Example 2 and Example 2 is that step (2) is different. Step (2) is changed to: at a flow rate of 50m 3 / h in an argon environment, the aerogel fiber web was carbonized, heated to 800°C at 9°C / min, kept warm for 3h, then placed in a 4wt% boric acid aqueous solution, soaked for 5.5h, dried at 90°C for 130min, and then heated to 2700°C at 12°C / min in a nitrogen atmosphere for graphitization treatment for 25s to obtain a graphite fiber web; the remaining steps are the same as in Example 2.
[0043] Comparative Example 3
[0044] The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: at a flow rate of 50m 3 / h in an argon environment, the aerogel fiber web was carbonized, the temperature was increased to 800°C at 9°C / min, kept warm for 3h, then continued to be heated to 1400°C, kept warm for 5h, continued to be heated to 1500°C, kept warm for 5h, then, in a nitrogen atmosphere, the temperature was increased to 2700°C at 12°C / min, graphitization treatment was carried out for 25s to obtain a graphite fiber web; the remaining steps are the same as in Example 2.
[0045] Comparative Example 4
[0046] The difference between Comparative Example 4 and Example 2 is that step (2) is different. Step (2) is changed to: at a flow rate of 50m 3 / h argon environment, the aerogel fiber net was carbonized, heated to 800°C at 9°C / min, kept warm for 3h, continued to heat to 1400°C, kept warm for 5h, continued to heat to 1500°C, kept warm for 5h, to obtain a carbon fiber net; the remaining steps are the same as Example 2.
[0047] Comparative Example 5
[0048] The difference between Comparative Example 5 and Example 2 is that step (3) is different. Step (3) is changed to: polyvinyl alcohol 1799, magnesium hydroxide, low-density polyethylene 2426H, diisopropylbenzene peroxide, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] are mixed in a mass ratio of 15:2.2:85:0.08:0.1 to obtain doped polyethylene; in an ozone environment with a concentration of 50 mg / L, the graphite fiber mesh is pretreated at 130°C for 3 minutes, and then the doped polyvinyl alcohol is coated on both sides of the graphite fiber mesh, irradiated for 15 minutes under a microwave power of 300 W, and cured at 75°C for 110 minutes to obtain a communication cable sheath material; the remaining steps are the same as in Example 2.
[0049] Comparative Example 6
[0050] The difference between Comparative Example 6 and Example 2 is that step (3) is different. Step (3) is changed to: polyvinyl alcohol 1799, magnesium hydroxide, low-density polyethylene 2426H, diisopropylbenzene peroxide, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] are mixed in a mass ratio of 15:2.2:85:0.08:0.1 to obtain doped polyethylene; the doped polyvinyl alcohol is coated on both sides of the graphite fiber mesh, irradiated for 15 minutes under a microwave power of 300 W, and cured at 75°C for 110 minutes to obtain a communication cable sheath material; the remaining steps are the same as those in Example 2.
[0051] Comparative Example 7
[0052] The difference between Comparative Example 7 and Example 2 is that step (3) is different. Step (3) is changed to: polyvinyl alcohol 1799, low-density polyethylene 2426H, diisopropylbenzene peroxide, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] are mixed in a mass ratio of 15:2.2:85:0.08:0.1 to obtain doped polyethylene; in an environment of ozone with a concentration of 50 mg / L and an ultraviolet wavelength of 254 nm, the graphite fiber mesh is pretreated at 130°C for 3 min, and then the doped polyvinyl alcohol is coated on both sides of the graphite fiber mesh, irradiated for 15 min under a microwave power of 300 W, and cured at 75°C for 110 min to obtain a communication cable sheath material; the remaining steps are the same as in Example 2.
[0053] Comparative Example 8
[0054] The difference between Comparative Example 8 and Example 2 is that step (3) is different. Step (3) is changed to: polyvinyl alcohol 1799, magnesium hydroxide, low-density polyethylene 2426H, diisopropylbenzene peroxide, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] are mixed in a mass ratio of 15:2.2:85:0.08:0.1 to obtain doped polyethylene; in an environment of ozone with a concentration of 50 mg / L and an ultraviolet wavelength of 254 nm, the graphite fiber mesh is pretreated at 130°C for 3 minutes, and then the doped polyvinyl alcohol is coated on both sides of the graphite fiber mesh and cured at 75°C for 110 minutes to obtain a communication cable sheath material; the remaining steps are the same as in Example 2.
[0055] Effect example
[0056] Table 1 below shows the performance analysis results of communication cable sheath materials obtained using Examples 1 to 3 of the present invention and Comparative Examples 1 to 8.
[0057] Table 1
[0058]
[0059]
[0060] From the comparison of the experimental results of the embodiment and the comparative example in Table 1, it can be found that the present invention uses an organic sol as a carbon source and mixes it with a silica sol as a silicon source. Non-covalent bond interactions are formed between the silica and cellulose molecular chains, and the mesopores and macropores in the cellulose structure are filled, so that the hybrid aerogel is more compact as a whole. After gel aging, a network structure with excellent three-dimensional skeleton is formed, thereby giving the matrix strong mechanical properties. Then, an aerogel fiber mesh is obtained through spinning, drying, and weaving. In the flowing argon gas, a silicon carbide layer is formed on the skeleton surface of the composite aerogel through solid-gas reaction and carbon thermal reduction reaction. As the temperature rises, uniformly dispersed silicon carbide nanoparticles are formed in the matrix, thereby forming a network carbon, silica, and silicon carbide ternary aerogel, so that the matrix achieves a flame retardant effect. Then, the fiber is graphitized again through high temperature, and a trace amount of boron is introduced in this process to form a carbon fiber on the fiber surface. It produces a protective effect and then enters the graphite matrix to fill the gaps between the hexagonal rings, thereby improving the crystallinity and graphitization degree, thereby enhancing the flame retardancy, heat resistance and mechanical properties. The fiber mesh is pretreated with ozone. Under the action of ultraviolet rays, the new ecological oxygen released by the decomposition of ozone is promoted, so that the surface of the graphite fiber is fully oxidized, and the surface area and roughness of the fiber are increased, and the mechanical bite on the interface is beneficial to improve the interface performance of the composite material. After treatment, the oxygen and nitrogen content of the fiber surface increases, and a majority of oxygen-containing polar groups are formed on the fiber surface, which improves its wettability with the resin and further enhances its chemical bonding with the resin; then, linear polymer polyvinyl alcohol doped with magnesium hydroxide is composited on both sides of the mesh. Under the action of microwave irradiation, the movement of polyvinyl alcohol molecules is promoted, and magnesium hydroxide is driven into the micropores of the aerogel, thereby enhancing the heat resistance, flame retardancy and mechanical properties of the material.
[0061] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A communication cable sheath material, characterized in that: The communication cable sheath material is prepared by mixing an organic sol and a silicon dioxide sol, and undergoing aging, spinning, drying, weaving, and high-temperature treatment to obtain a graphite mesh, which is then compounded with polyvinyl alcohol.
2. A method for preparing a communication cable sheath material, characterized in that: The method comprises the following preparation steps: (1) mixing an organic sol, a silica sol, and 3-aminopropyltrihexyloxysilane, heating the mixture to 67-72°C at 10°C at a rate of 2-3°C / h, performing gel aging treatment, and then wet spinning the mixture into a deionized water coagulation bath, coagulating for 1-3 hours, removing the mixture, immersing the mixture in tert-butyl alcohol, standing the mixture for 3-6 hours, rinsing the mixture with deionized water for 5-10 times, drying the mixture with carbon dioxide supercritical fluid, and weaving the mixture into a web to obtain an aerogel fiber web; (2) The aerogel fiber web is carbonized and then placed in a 4 wt % boric acid aqueous solution for 4 to 7 h, dried at 80 to 100 ° C. for 100 to 160 min, and then heated to 2400 to 3000 ° C. at 8 to 15 ° C. / min in a nitrogen atmosphere for graphitization for 18 to 30 s to obtain a graphite fiber web; (3) The graphite fiber mesh is pretreated under ultraviolet conditions of 254 nm, and then doped polyvinyl alcohol is coated on both sides of the graphite fiber mesh. The mesh is irradiated for 10 to 20 minutes under a microwave power of 200 to 400 W, and cured at 60 to 85° C. for 70 to 150 minutes to obtain a communication cable sheath material.
3. The method for preparing a communication cable sheath material according to claim 2, characterized in that: The preparation method of the organosol described in step (1) is as follows: sodium hydroxide, urea and deionized water are mixed in a mass ratio of 7:12:100, cooled to 10-15°C, short cotton wool with a mass of 0.3-0.6 times that of the sodium hydroxide and chitosan with a mass of 0.08-0.12 times that of the sodium hydroxide are added, stirred at 200-500rpm for 10-20min, then sheared at 100-200rpm for 15-30min, sodium periodate with a mass of 0.04 times that of the sodium hydroxide is added, stirred at 70-120rpm for 10min, 8wt% o-phthalaldehyde-ethanol solution with a mass of 8-12 times that of the sodium hydroxide is added, and stirring is continued for 10min to obtain the organosol.
4. The method for preparing a communication cable sheath material according to claim 2, characterized in that: The process parameters of the wet spinning in step (1) are: the spinneret aperture is 0.07-0.12 mm, and the spinning speed is 200-350 m / min.
5. The method for preparing a communication cable sheath material according to claim 2, characterized in that: The temperature of the carbon dioxide supercritical fluid drying in step (1) is 50-65° C. and the gas pressure is 13-19 MPa.
6. The method for preparing a communication cable sheath material according to claim 2, characterized in that: The weight of the mesh in step (1) is 70-100 g / m 2 .
7. The method for preparing a communication cable sheath material according to claim 2, characterized in that: The mass ratio of the organic sol, silica sol and 3-aminopropyltrihexyloxysilane in step (1) is 7:7:
1.
8. The method for preparing a communication cable sheath material according to claim 2, characterized in that: Step (2) of the carbonization treatment step: at a flow rate of 40 to 60 m 3 / h in an argon environment, heat up to 700-850°C at 5-12°C / min, keep warm for 2.5-4h, continue to heat up to 1400°C, keep warm for 5h, continue to heat up to 1500°C, keep warm for 5h.
9. The method for preparing a communication cable sheath material according to claim 2, characterized in that: The pretreatment conditions in step (3) are: ozone concentration of 50 mg / L, temperature of 100-150° C., and time of 1-5 min.
10. The method for preparing a communication cable sheath material according to claim 2, characterized in that: The doped polyvinyl alcohol in step (3) is prepared from polyvinyl alcohol 1799, magnesium hydroxide, low-density polyethylene 2426H, diisopropylbenzene peroxide, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] in a mass ratio of 8-20:1.5-3:80-90:0.05-0.1:0.05-0.2.
Citation Information
Cited By
High-performance multifunctional cable and preparation method thereof
CN120854050A